MORFOLOGI KELENJAR AKSESORIS KELAMIN BIAWAK AIR (Varanus salvator bivittatus) JANTAN - Mahfud .; Adi Winarto; Chairun Nisa (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2019)
The study was aimed to describe the macromorphological and micromorphological aspect of the accessories gland of Male Varanus salvator bivittatus. Two adult male lizards with 45.60 cm SVL were used in this experiment. The animals were sacrificed by exsanguination under deep anesthetized and fixed in 4 % paraformaldehyde through perfusion and then its visceral site was observed. Histomorphological evaluation was obtained by paraffin preparation with section thickness of 3-4 μm then stained in Hematoxylin-Eosin (HE), Alcian Blue (AB) pH 2.5 and Periodic Acid Schiff (PAS). The result showed that accessories gland which was found at the dorsal of cloaca, specifically at the caudal end of deferent duct that was a hemipenile bulge. Microscopically, the accessories gland was identified as tubular mucous type gland which was resemble to bulbourethral gland in mammals. The cytoplasm of the secretory cells showed weak reaction, while strong reaction was observed in the luminal mucus which was stained by AB staining. In contrast, luminal mucus showed a weak reaction to PAS staining. In conclusion, V. salvator bivittatus has only one accessory gland and its microanatomical structure resembled the bulbourethral glands.